Content Marketing, Customer Engagement On Marketing Performance Mediated By Digital Marketing In Batik Msmes In Banyumas Regency - Reza Rahmadi Hasibuan; Najmudin Najmudin (Cita konsultindo, 2024)
Banyumas Regency, which is known for its rich batik culture, is one of the areas where batik MSMEs are trying to maintain and develop their market amidst intense competition. This research has not yet discussed mediation of marketing performance, so the novelty in this research is that digital marketing becomes mediation. This research was conducted on Batik MSMEs in Banyumas Regency by giving questionnaires to business owners and MSME managers using Google Form. The Banyumas Regency Cooperatives and MSMEs Service said there were 120 MSMEs. In this study, the entire population was used as the research sample. This is because there are only 120 Batik MSMEs in Banyumas Regency. Partial Least Square (PLS) model analysis was used in this research. Based on the research results, it can be concluded that content marketing has no effect on digital marketing. Content marketing has no effect on marketing performance. Customer engagement influences digital marketing. Customer engagement influences marketing performance. Digital marketing influences marketing performance. Digital marketing does not mediate the relationship between content marketing and marketing performance and digital marketing mediates the relationship between customer engagement and marketing performance.